Mechanical, Durability and Microstructural Properties of GGBFS-RHA Based Geopolymer Concrete Cured in Ambient Condition. Issue 4 (5th October 2018) - Zabihi, Seyed Mahmoud; Tavakoli, Hamid Reza
Abstract : The current study aims to attain ground granulated blast-furnace slag (GGBFS) and rice husk ash (RHA) based geopolymer concrete convenient for construction of structural elements by using high amounts of industrial and agricultural solid waste as a by-product material. Compressive and splitting tensile strength, shrinkage and rapid chloride permeability tests were carried out to investigate the geopolymer properties. The test results indicated that replacement of GGBFS-RHA based geopolymer improved the mechanical properties of concrete and 100% replacement of geopolymer can be taken into account having the best results from environmentally, structurally and economically point of view. Furthermore, curing time affected the compressive strength significantly. In addition, considerable CO2 would be emitted for construction of studied sustainable GGBFS-RHA based geopolymer composites. Moreover, from microstructural point of view, totally incorporation of GGBFS-RHA based geopolymer in composites led to pore refinement in both the matrix and the interfacial zones, and a reduction in the width of the interfacial transition zone (ITZ) between the paste and the aggregate, which could efficiently reduce the water permeability.